Who is hit hardest during a financial crisis? The vulnerability of young men and women to unemployment in an economic downturn - Sher Verick (Institute for the Study of Labor (IZA), 2009)
The current financial and economic crisis has resulted in the worst global recession since World War II. The subsequent destruction of jobs and increased duration of joblessness will ensure that unemployment across the world will continue to rise and stay stubbornly high for some time to come, well after the economy has begun to recover. Beyond this generalization, such downturns have more adverse implications for vulnerable segments of the population such as youth. As presented in this paper, data for both the current and previous financial crises reveals that young people are indeed hit hardest as reflected by rising unemployment rates, which persist long after the economy is growing again. In the wake of the present downturn, young men have been particularly affected, which has been driven by a range of factors including the high proportion of young men in heavily impacted sectors such as construction. In response to this situation, policymakers should utilize targeted crisis interventions that aim to keep youth employed where possible, while also assisting new entrants and those who have lost jobs find employment (or at a minimum stay attached to the labour force), particularly as the economy recovers.
urn:nbn:de:101:1-20091105792
Keywords: G01; J21; J64; J68; 330; Unemployment; youth unemployment; financial crisis; Finanzmarktkrise; Wirtschaftskrise; Arbeitslosigkeit; Jugendarbeitslosigkeit; Industriestaaten